Excellent Front Desk Agent Service in Increasing Guest Satisfaction at Hotels in Bali - Venysia, Ni Putu Selina; Sekarti, Ni Ketut; Darmawijaya, I Gede (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to identify and group guest reviews of Front Desk Agent services at one of the hotels in Bali that provide a pleasant experience (Prima/WOW). Data was collected from guest reviews on OTA Tiket.com and Tripadvisor in the period January 2023 to May 2024. The results of the analysis showed four main themes that were prominent in guest reviews: The first theme,